The first Philippine species of Loeblites Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
Loeblites Franz, 1986 is a genus of Glandulariini with adults sharing a very similar body form and most taxonomically important structures with Syndicus Motschulsky, 1851. One of the most conspicuous differences between these genera is the antennal structure. In Syndicus, the antennomere XI is strongly reduced, much shorter than X and lacks the basal stalk, so that the two terminal antennomeres are compactly assembled. They either form one oval structure that appears as a single antennomere because the base of subconical antennomere XI is as broad as apex of X (Syndicus s. str.) or the antennomere XI forms a distinct small ’papilla’ on top of X (subgen. Semisyndicus Jałoszyński, 2004) because the base of antennomere XI is much narrower than apex of X. Adults of Loeblites have unmodified antennae, with the antennomere XI strongly elongate and with a narrow basal stalk; additionally the antennae are strikingly slender, nearly filiform. Morphological structures of both genera were described and illustrated by Jałoszyński (2004, 2005). While Syndicus is species-rich, often abundant in leaf litter and under bark in subtropical forests (Jałoszyński 2004, 2006, 2008, 2009, 2011, 2014; Jałoszyński & Nomura 2006; Yin & Li 2015; Yin et al. 2014; Yin & Zhou 2016; Zhou & Yin 2017), and broadly distributed from southeastern Australia, through Southeast Asia, Yunnan (China) and Ryukyus (Japan), up to Sri Lanka, India and the Himalayas, Loeblites comprises merely four species known to occur in Malaysia, Thailand and China (Jałoszyński 2005; Zhou & Li 2015). Loeblites mastigicornis Franz, 1986 is known to occur in Chiang Mai (northern Thailand), L. sabahensis Franz, 1992 and L. minor Jałoszyński, 2005 in Sabah (northern Borneo), and L. chinensis Zhou & Li, 2015 in Yunnan (southwest China). Two females representing an undescribed species were also recorded from Yunnan by Zhou & Li (2015). Specimens of this interesting genus are found rarely, in small numbers and they are typically sifted from leaf litter in subtropical forests.